Criteria for Cerebrospinal Fluid Diversion in Retractorless Sphenoid Wing Meningioma Surgery: A Technical Report - Vetsa, Shaurey; Nadar, Arushii; Vasandani, Sagar; Gorelick, Evan; Bungard, Jillian; Barak, Tanyeri; Fulbright, Robert K.; Marianayagam, Neelan J.; Moliterno, Jennifer (Journal of Neurological Surgery Reports, 2022)
Objective Sphenoid wing meningiomas (SWMs) can present surgical challenges, in that they are often obscured by overlying brain, encase critical neurovascular structures, and obliterate cerebrospinal fluid (CSF) cisterns. While brain retraction can enable access, its use can have potentially deleterious effects. We report the benefits and outcomes of the criteria we have developed for use of cerebrospinal diversion to perform retractorless surgery for SWMs.Design Technical report.Setting Yale School of Medicine and Yale New Haven Hospital.Participants Between May, 2019 and December, 2020, ten consecutive patients were included who met the presented criteria for SWM surgery with preoperative lumbar drain (LD) placement.Main Outcome Measures Length of hospital stay, surgical complications, and extent of resection.Results We have developed the following criteria for LD placement in patients with SWMs such that LDs are preoperatively placed in patients with tumors with one or more of the following criteria: (1) medial location along the sphenoid wing, (2) vascular encasement resulting in obliteration of the optic carotid cistern and/or proximal sylvian fissure, and/or (3) the presence of associated edema. CSF release, after craniotomy and sphenoid wing removal, allowed for optimization of exposure, leading to the maximal safe extent of tumor resection without brain retraction or any complications.Conclusions Preoperative LD placement is effective in allowing for maximal extent of resection of SWMs and may be considered in cases where local CSF release is not possible. This technique is useful in those tumors located more medially, with encasement of the vasculature and/or associated with edema.
Keywords: meningioma; CSF diversion; skull base surgery; lumbar drain